Risk Analysis of Catfish (Clarias sp) Breeding in The Fish Hatchery Unit of Mulyorejo I, Malang Regency, East Java - Ega Putri Prahestin; Nuddin Harahab (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
Production risk causes the income of catfish seed cultivator in UPR Mulyorejo I is not maximum, so it is necessary to identify the problem of production risk by knowing the type, probablility and impact of production risk and its handling strategy. The method used is descriptive survey method using primary and secondary data. Primary data by observing directly on the location of research and observation data collection techniques, interviews, questionnaires, and documentation. The result of analysis shows that there are four sources of risk in UPR Mulyorejo I that are seasonal change, water quality, disease and pest with probability 32%, 30%, 27%, and 19%, with risks of IDR 1,200,568, IDR 983,952, IDR 840,531, and IDR 355,725. Seasonal changes and water quality is a risk of having a high probability that the need for special handling from the farmers.